2020
DOI: 10.15403/jgld-768
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Esophagitis: Diagnosis and Current Management

Abstract: Eosinophilic esophagitis (EoE) is an eosinophil-rich, Th2 antigen-mediated disease of increasing worldwideprevalence. Originally considered common in children and young adults, it can be seen at any age, withthe highest prevalence between 30 and 40 years. Symptoms reflect esophageal dysfunction, and typicalendoscopic pictures consist of rings, furrows, exudates and edema. Progressive disease leads to pathologictissue remodeling, with ensuing esophageal rigidity and loss of luminal diameter caused by strictures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 110 publications
0
17
0
3
Order By: Relevance
“…Symptoms reflect esophageal dysfunction, and characteristic endoscopic appearances consist of rings, furrows, exudates, and edema. Progressive disease leads to pathologic tissue remodeling, with ensuing esophageal rigidity and loss of luminal diameter caused by strictures [102]. Until recently, patients with esophageal eosinophilia responding to PPIs (PPI-REE) were excluded from the EoE spectrum [103].…”
Section: Eosinophilic Esophagitis: a Role For Vonoprazan?mentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms reflect esophageal dysfunction, and characteristic endoscopic appearances consist of rings, furrows, exudates, and edema. Progressive disease leads to pathologic tissue remodeling, with ensuing esophageal rigidity and loss of luminal diameter caused by strictures [102]. Until recently, patients with esophageal eosinophilia responding to PPIs (PPI-REE) were excluded from the EoE spectrum [103].…”
Section: Eosinophilic Esophagitis: a Role For Vonoprazan?mentioning
confidence: 99%
“…Several retrospective and prospective studies have reported histological remission and symptom improvement (even with persistent eosinophilic infiltration) after an 8-week treatment course with PPIs, with established GERD having a higher chance of responding to PPIs (for review see [102]). A meta-analysis of 33 studies, including 619 patients (431 adults and 188 children) found an overall histologic remission and clinical response of 50.5% and 60.8%, respectively [106].…”
Section: Eosinophilic Esophagitis: a Role For Vonoprazan?mentioning
confidence: 99%
“…52 The idea of trying PPI therapy in patients with EoE arose from the observation that a subset of GERD patients present with esophageal eosinophilia, 22,53 which is usually located in the distal esophagus but rarely reaches the high density commonly observed in EoE. 54 As mentioned previously, the original aim of acid suppression in patients with EoE was to eliminate GERD as an alternative cause of eosinophilic infiltration. However, it became clear that the relationship between esophageal eosinophilia, EoE, and GERD was not this simple 40 and that the overlapping symptoms of these disorders made definitive clinical diagnosis challenging.…”
Section: Eoe Treatmentmentioning
confidence: 99%
“…These characteristics include linear furrows (vertical lines), esophageal rings (concentric rings), edema (decreased vascularity), plaques (white spots, exudates), strictures, and a crepe paper-like esophagus (mucosal fragility). 2 Hirano et al proposed an endoscopic classification system for EoE in an attempt to standardize the method of endoscopic diagnosis (Table 1). 3 Based on this classification, an endoscopic reference scoring system referred to as EREFS (an acronym consisting of exudates, rings, edema, furrows, and strictures) was created.…”
Section: Answermentioning
confidence: 99%